Entrepreneurial Commitment among Youth Entrepreneurs: The Role of Individual, Social, and Contextual Factors - Husna, Aftina Nurul; Az Zahra, Aning (Journal of Social and Industrial Psychology, 2025)
Entrepreneurial commitment is a relatively new topic in entrepreneurship studies. Although its role is crucial as a bridge between entrepreneurial intention and action, research on this variable from a psychological perspective remains limited, especially in Indonesia. Grounded in social cognitive theory and career-life preparedness, this study investigates the influence of individual factors (gender, motivation, entrepreneurial characters, self-efficacy, and protean career orientation), social (perceived family support and involvement in family business), and contextual (business status, perception of employability, and Person-Entrepreneurship Fit) on entrepreneurial commitment. A total of 95 young adults who were university students, aged 18–25, owned a business and came from entrepreneurial families were recruited through convenience sampling in a cross-sectional survey. The variables in this study were measured using psychological scales that have been psychometrically validated. The results of the regression analysis showed that, out of the ten variables tested, entrepreneurial motivation, Protean career orientation, family support, involvement in the family business, and Person-Entrepreneurship Fit in the dimension of skill fit had a significant influence on entrepreneurial commitment. Although differences in commitment scores were found based on gender and business ownership status, these two variables did not show significant effects in the regression model. These findings lay the foundation for future studies on strategies to enhance entrepreneurial commitment and the role of commitment in improving business performance, as well as the development of evidence-based entrepreneurship education programs for the younger generation.